Scorpion Venom and the Inflammatory Response - Vera L. Petricevich (Mediators of Inflammation)
Scorpion venoms consist of a complex of several toxins that exhibit a wide range of biological properties and actions, as well as chemical compositions, toxicity, and pharmacokinetic and pharmacodynamic characteristics. These venoms are associated with high morbility and mortality, especially among children. Victims of envenoming by a scorpion suffer a variety of pathologies, involving mainly both sympathetic and parasympathetic stimulation as well as central manifestations such as irritability, hyperthermia, vomiting, profuse salivation, tremor, and convulsion. The clinical signs and symptoms observed in humans and experimental animals are related with an excessive systemic host inflammatory response to stings and stings, respectively. Although the pathophysiology of envenomation is complex and not yet fully understood, venom and immune responses are known to trigger the release of inflammatory mediators that are largely mediated by cytokines. In models of severe systemic inflammation produced by injection of high doses of venom or venoms products, the increase in production of proinflammatory cytokines significantly contributes to immunological imbalance, multiple organ dysfunction and death. The cytokines initiate a cascade of events that lead to illness behaviors such as fever, anorexia, and also physiological events in the host such as activation of vasodilatation, hypotension, and increased of vessel permeability.